Impact of Management Change on the Quality of Health Service: A Case Study on Ahmed bin Agila Hospital Laghouat - Charef , Abdelkader (The Arab Journal of Administration, 2018)
Trying to organizations depending on their activities and their business and in order to achieve competitiveness and sustainability to make changes to cope with the pressures of the external environment, or those caused by Internal Environment. But often and find this ambition to change the resistance or concerns and this has to be the fear that this addresses follow an appropriate strategy for change, Quality in health care means to satisfy patients and their families by meeting the requirements of treatment and to secure appropriate care for the patient and good to deal with the patient and his visitors. It should health care providers of health care professionals to be well-educated and well-trained to cope with the daily challenges of meeting the needs and expectations of their clients. Health care is a complex field, and is not available for health workers good technical culture, it weakens their chance to enjoy the confidence of their patients, Hence, we need quality health care to be associated with the capabilities and qualifications of high-level technology. Moreover, it is important to realize that the quality of health care is a process and not a program. It should be initiated, and submission, evaluation and improvement, monitored constantly, even after the patient recovers from his illness. This study aimed to identify the extent of the health institution’s dependence on change management to improve the quality of provided health service, and to achieve this goal a field study conducted on hospital public institution Ahmed bin Agila Laghouat, the sample included the following categories: doctors, administrators, and agents of the medical similarities, and individuals who are working in other jobs in the institution, which was followed descriptive analytical approach in this field study by designing a form and distributed to a random sample, retrieved 62 form, then the data using appropriate statistical methods analyzing, and at last been reached that there is a trace of change management on the quality of health service of the institution under study.